Analysis Of Knowledge And Attitude Of Lung Tb Patients With Anti Tuberculosis Drug Compliance - Dian Novita Hanggi (Chakra Brahmanda Lentera Institute, 2020)
Pulmonary tuberculosis is a direct infectious disease caused by the germ of Tuberculosis (Mycobacterium Tuberculosis). One of the determinants of the successful management of tuberculosis therapy is patient compliance with therapy. Non-compliance with treatment will cause failure and recurrence, resulting in resistance and continuous transmission of disease. The aim is to find out whether there is a relationship between knowledge and attitude of pulmonary tuberculosis patients with adherence to taking anti-tuberculosis medication in the Isolation Room at Mokoyurli General Hospital, Kab. Buol The design used in this study is Cross Sectional. The population is all patients with pulmonary TB. The sample size was 41 respondents using purposive sampling technique. Independent research variables are knowledge and attitudes. The dependent variable is compliance. Data were collected using a questionnaire, then data were analyzed using the rho spearment test with a significance level of α ≤ 0.05. The results showed that most of the respondents before the intervention had disobedience as many as 25 respondents (65.8%), after the intervention had obedience as many as 28 respondents (73.7%), the statistical test in the study between the variables of knowledge with compliance using a spearment rho test with a <0.05 obtained p = 0,000 where H1 was accepted and H0 was rejected, which means that there is a relationship between Lung TB Patients Knowledge and Compliance with Taking Anti-Tuberculosis Medication in the Isolation Room at Mokoyurli General Hospital, Kab. Buol, a statistical test in the study between attitude variables with adherence using the rho spearment test with a <0.05 obtained p = 0,000 where H1 was accepted and H0 was rejected, which means that there is a relationship between the attitude of pulmonary TB patients with adherence to taking anti-tuberculosis drugs in the Isolation Room of the General Hospital Mokoyurli District. Buol There is a relationship of knowledge and attitudes of pulmonary tuberculosis patients with adherence to taking anti-tuberculosis drugs in the Isolation Room at Mokoyurli Public Hospital, Buol